Perniagaan Muafakat with Tawakkal (Reliance on Allah) and Ummatic (Collectiveness) - Yahya, Rohaziah; Mhd Sarif, Suhaimi; Zainudin, Dolhadi; Ismail, Yusof (IIUM Journal of Case Studies in Management, 2025)
Perniagaan Muafakat, a sole proprietorship established by Haji Muafakat, exemplifies the values of mutual assistance (muafakat), communal responsibility (fardu kifayah), and unwavering faith in Allah's providence. Originating as a modest grocery shop, the business expanded into various essential services, including a bakery, printing center, laundry, hardware store, and trading entity. Each venture was created in response to the local community's needs, prioritizing service over profit. This case study explores the challenges faced by Perniagaan Muafakat, from competition with large malls to the disruptions caused by the COVID-19 pandemic. Through dialogue with family, employees, and community stakeholders, Haji Muafakat embraced innovation, including digital tools and loyalty programs, while preserving the personal touch that built trust among customers. His dedication to amal soleh (good deeds) and syukur (gratitude) ensured that the business remained a pillar of support for the community. This narrative highlights the importance of ethical entrepreneurship grounded in Islamic principles, showcasing how faith, resilience, and collaboration can sustain a business and uplift a community in challenging times. Keywords: Diversification, Tawakkal, Ta’awun, Ummatic